Woman Entrepreneurial Orientation Based on Synthetic Scooping Review - Margo Purnomo; Maulina, Erna; Reza Damayanti; Ramadhan, Rega; Alamsah, Untung; Shalihah, Afifah; Nina, Siti Ma’ani; Komariah, Lilis (School of Business, IPB University (SB-IPB), 2023)
The research uses the synthetic scoping review method to reveal a state-of-the-art entrepreneurial orientation study in social entrepreneurship context. This research was carried out in a mixed method approach with three stages: a systematic review and scoping review as a qualitative approach and bibliometric mapping with co-occurrence analysis as a quantitative approach. The results of a systematic review show that a social entrepreneurial orientation has been initiated since 1906. In Spain and the United States, quantitative research dominates. The scoping review results reveal seven dimensions of entrepreneurial orientation typical in the social entrepreneurship context. Furthermore, the results of the co-occurrence analysis raise five major themes, namely 1) women entrepreneurial orientation and women empowerment, 2) the dimension of women entrepreneurial and get new dimensions are women flexibility and women ethics, 3) women entrepreneurial orientation and intangible resources, 4) women entrepreneurial orientation and family to work conflict, 5) business performance. Keywords: women empowerment, dimension of women entrepreneurial orientation, intangible resources, family to work conflict, business performance